Analysis of Ergonomic Parameters in Architectural Design Studios: A Case Study of Bursa Technical University - Gümüş, İmran; Köse, İstem Seçkin Parlakyıldız (My University, 2025)
Ergonomics encompasses physical, psychological, and environmental factors, with a crucial role in educational settings. Design studios, integral to architecture, interior architecture, and urban planning education, must ensure optimal spatial, visual, auditory, and thermal comfort to foster creativity and technical skills. This study evaluates the design studios at Bursa Technical University’s Faculty of Architecture and Design, assessing ergonomic conditions through technical measurements and user satisfaction surveys. Findings reveal that repurposed spaces used as design studios fail to meet essential ergonomic standards, impacting students’ learning experiences. The study highlights deficiencies in spatial organization, lighting, acoustics, and thermal conditions, emphasizing the need for improvements. By addressing these shortcomings, the research aims to guide the optimization of design studios as dynamic educational environments supporting technical drawing, group critiques, model-making, and workshop activities. The study is expected to serve as a guiding reference for the organization of design studios in accordance with ergonomic standards.
Keywords: Ergonomics; visual comfort; thermal comfort; design studios; auditory comfort